PREDICTION OF ACTIVE SITES IN SOME CANCER RELATED PROTEINS BY CARD ANALYSIS - K.AKILA; S.RAJASREE; R.SHANTHAKUMAR (International Journal of Pharma and Bio Sciences, 2014)
Carbon is the element that contributes towards the hydrophobic effect and biological function of living systems. It is reported that globular proteins prefer to have 31.45% carbon for stability, which can be used as the standard for carbon measurement and comparison. Carbon distribution analysis has been carried out using the tool CARd, which can clearly identify the hydrophobic and hydrophilic regions along the sequence and can also pinpoint an amino acid which is causing instability. Cancer is one of the most feared diseases of the 20th century and spreading further with continuance and growing incidence in 21st century. The role of carbon along the protein sequence and amino acid composition of hydrophobic regions in selected cancer related proteins (BAK, PTEN, E6, p53, Retinoblastoma) were focused in this study. Carbon content and distribution were computed and the active sites identified were reported here. This study which dealt with the active site prediction through the analysis of carbon distribution in cancer related proteins promises significant applications in biological and pharmaceutical sciences such as drug design and genetic engineering.